REALIZACJA MIĘDZYNARODOWYCH STANDARDÓW OCHRONY DZIEDZICTWA KULTURALNEGO W POLSKIEJ USTAWIE O OCHRONIE ZABYTKÓW I OPIECE NAD ZABYTKAMI - Gerecka-Żołyńska, Anna (Wydział Prawa i Administracji UAM, 2007)
The paper presents the Polish model o f monument protection and its short genesis described in the systematic order of the Act on protection and care of monuments of 2003. First, issues related to the object of protection have been identified, with particular focus put on the status of objects of special archaeological value. This was done because interesting solutions adopted in regard those objects, with respect to the conditions of excavations, and the duties and obligations arising from their discovery and the need for securing archaeological findings have been reflected in the text of the Polish Act. After that, consequences resulting from the distinguishing of two notions: „protection” and ‘care’ have been shown., with an indication, that the Act introduced the notion of „care” in respect of monument protection in the Polish model for the first time. Further, in the same context, the issue of restitution of monuments unlawfully taken away from the state with legal rights to them, as well as novel solution adopted in that respect by the European Union and subsequently incorporated universally as UNIDROIT have been mentioned. It is also stressed that the Polish Act has incorporated the full scope of the solutions developed by the European Commission. Finally, the valuable initiative proposed by UNESCO and aimed at protection of monuments has been presented, and namely the creation of the „World Heritage List”, and related to it „World Heritage in Danger List” . While the former is mainly of a prestigious character, the latter offers concrete financial support necessary for rescuing selected monuments all over the world, and therefore also in Poland.
INCORPORATION OF INTERNATIONAL STANDARDS OF CULTURAL HERITAGE PROTECTION IN THE POLISH ACT ON PROTECTION AND CARE OF MONUMENTS